Effects of the Temporal Scale of Observation on the Analysis of Aquatic Invertebrate Metacommunities - Castillo-Escrivà, Andreu; Mesquita-Joanes, Francesc; Rueda, Juan (Frontiers in Ecology and Evolution, 2020)
The development of metacommunity theory has boosted the implementation of numerous empirical tests with field data, mostly focused on the role of spatial and environmental gradients on metacommunity organization. These studies showed an important dependence of the results on the observational scale considered, i.e., spatial grain, sampling spacing, and extent. However, few works deal with time per se as a component explaining metacommunity structure, even when data from periodic sampling are available. We suggest adding time explicitly to metacommunity analysis, but taking into account that the temporal scale of observation could affect the estimation of the relative influence of environment, space, and time, as previously recorded for spatial scale variation. Here, we analyze temporal scale dependence using simulated and empirical metacommunities of aquatic invertebrates. The effects of the study duration (i.e., temporal extent) were stronger when most metacommunity variation occurred along the temporal axis, so that local communities were spatially homogenized under high dispersal rates. Contrarily, dispersal limitation and niche differentiation (depending on the spatio-temporal structure of the environment) kept constant the spatial heterogeneity of the metacommunity, reducing the temporal variation and the importance of the temporal scale of observation. Our results highlight the importance of the temporal scale chosen for the analysis of metacommunity dynamics and emphasizes the temporal perspective of metacommunities, suggesting novel and interesting avenues in this research program.